AVALIAÇÃO DO COMPORTAMENTO REPRODUTIVO DE DUAS ESPECIES DE PEIXES ISCAS DO PANTANAL - ALMEIDA, Mizael Pereira; CAITANO, Welisson Aparecido Bispo; MELCHER, Larissa; SANTOS, Jussara Garrido; WANDERLEY, Alysson Martins (ANAIS DO ENIC, 2026)
.